Differences on Prosaccade Task in Skilled and Less Skilled Female Adolescent Soccer Players - Zhou, Junyi (Frontiers in Psychology, 2021)
Although the relationship between cognitive processes and saccadic eye movements has been outlined, the relationship between specific cognitive processes underlying saccadic eye movements and the skill level of soccer players remains unclear. The present study investigates the difference in saccadic eye movements in skilled and less skilled Chinese female adolescent soccer players by using the prosaccade task. The results indicated that skilled soccer players exhibited shorter saccade latency, decreased variability of saccade latency and higher spatial accuracy of saccade than their less skilled counterparts. The implications of these findings for cognitive capacities and the attentional system of soccer players are discussed.